Cluster router based on eccentricity - Zhanabaev, Z.Zh; Akhtanov, S.N; Turlykozhayeva, D.A; Ussipov, N.M; Ibraimov, M.K. (KU Publ, 2022)
In this paper, a cluster router based on eccentricity was worked out, related to the field of telecommunications, especially, to the field of message transmission. Messages in this router are transmitted as packets along the route specified in it between devices connected to the network. Each node in this network is assigned a unique address, thanks to which routing can be accelerated. Each router forms a routing map, thanks to the calculated eccentricity of nodes, with which the physical route of the packet is selected at the logical address of the cluster. In addition, the routing map is stored in the register and non-volatile memory of the device to prevent information loss. To analyze this cluster device, a fractal analysis of the UV-flower model network was carried out and the information dimensions of Tsallis and Renyi were calculated
Keywords: cluster router; eccentricity; complex networks; box covering algorithms; Tsallis and Renyi dimensions